Entrepreneurship : Creative Carpet / Anuar Mohd Yusof ... [et al.] - Mohd Yusof, Anuar; ldris, Mohammad Ariff; Sarip, Mohd Yusrin; Mohd Afkar, Abdul Kadir; Hassan, Abdul Razak (2002)
The Creative Carpet Sdn. Bhd. is operating as one of the marketing company that concerned on selling various carpet products. The objective of our business is to introduce to our new generation to be more concern about the important and function of carpet. It is in form of fives partner base on partnership rules.